Pelaksanaan Penyimpanan Berkas Rekam Medis Berdasarkan Unsur Manajemen 5m Di RskiaPermata Bunda Yogyakarta - Pujilestari, Anik; , Sri Darnoto S.KM M.PH; , Arief Kurniawan NP, SKM, M.PH (2016)
Medical record file storage management is very important for health care institution. According to the results of interviews with the chief officer in the medical record in RSKIA Permata Bunda Yogyakarta, there are some missfile on filing shelves that make service to patients become long. The research is descriptive qualitative, it means ollecting data by direct observation of the research. The methods are interviews and observation. Collecting data using primary data. In the elements of man, medical record officer who completed D3 medical record is one person and four people who are not. In the elements of money, nothing specific budget on medical record file storage. In the elements of methode, using decentralized storage systems and alignment system using straight numeric filing. In the elements of Machine, there is no tracer to mark out a medical record file. In the elements of Material, outpatients medical record file using quarto paper. Storage shelves using iron shelves and there are no folders on the outpatient medical record file.